Assessing the Social and Economic Vulnerability of Farmers by Group Categories in Volcano-Prone Disaster Area in Sempu Village, Kediri Regency - Ayuni, Ita Kurata; Hizbaron, Dyah Rahmawati; Sudrajat, Sudrajat (TDMRC, Universitas Syiah Kuala, 2024)
Agriculture is the main livelihood of residents in Sempu Village, Ngancar District, Kediri Regency. Agriculture in this region has a high level of disaster risk because it is located in the disaster-prone area of Mount Kelud. The potential for damage to agricultural land due to the Kelud volcanic eruption will increase the vulnerability of farmers. Vulnerability assessment is important because one of the efforts to reduce disaster risk is to reduce vulnerability. Vulnerability assessments are often carried out on heterogeneous societal subjects and not based on specific subjects or professions. In fact, farmers are a profession that is more vulnerable than other professions and have various characteristics that can influence vulnerability. Therefore, this research aims to examine socio-economic vulnerability with a greater focus on farmers to find out how vulnerable farmers in Sempu Village are and what characteristics farmers are most vulnerable to. This research uses scoring and weighting methods using AHP (analytical hierarchy process) to analyze data and survey methods to collect data. The results of the vulnerability assessment show that 77% of farmers in Sempu Village have low social vulnerability. As many as 52% of farmers have moderate economic vulnerability, 31% have high economic vulnerability. Elderly farmers in Sempu Village have the highest level of social vulnerability. Farmers who have limited land and loan capital have the highest level of economic vulnerability. Women farmers show higher levels of social and economic vulnerability than all farmers.